Peningkatan Kebugaran Jasmani dan Konsentrasi Siswa Melalui Model Fitness Education dalam Pembelajaran PJOK - Muhammad Salman Nurdin; Lukmannul Haqim Lubay; Wildan Alfia Nugroho; Suherman Slamet (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the effectiveness of the Fitness Education model in improving physical fitness and to analyze its effect on students' learning concentration in Physical Education (PJOK) classes. The study employed a quantitative approach with an experimental design. The sampling technique used was total sampling, involving all 82 fifth-grade students of SDN 065 Cihampelas. The research instruments included the Indonesian Physical Fitness Test (TKJI) and the Concentration Grid Test (CGT). The results showed that the implementation of the Fitness Education model improved students’ physical fitness and learning concentration. In conclusion, the Fitness Education model is effective in enhancing physical fitness and learning concentration among elementary school students in Physical Education classes. Keywords: Concentration Grid Test, Fitness Education, Physical Fitness, Learning Concentration, Elementary School Students